Pengaruh Love Of Money, Religiusitas Dan Idealisme Terhadap Persepsi Mahasiswa Akuntansi Tentang Etika Akuntansi - Ni Putu Ari Yani; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2023)
Accounting students are prospective accountants who are expected to have a positive impact on society. When students behave ethically can anticipate the form of irregularities committed by further accountants. This study was conducted to determine and analyze what things affect the perception of accounting students about the ethical crisis of accountants. Some things that can affect the perception of accounting students are Love of Money, religiosity and idealism. The population in this study were students of The Hindu University of Indonesia with the number of 2019 classes of 112 students and the 2020 class of 88 students, making the total population of 200 students. The multiple Linear regression is analysis method. The results of this study are love of money, religiosity and idealism positive and significant effect on the perception of accounting students about the ethical crisis of accountants. It is expected that the next researcher when doing a similar study, in order to add variables that have not been included in this study in order to obtain a stronger influence.